Acute effect of metipranolol on the retinal circulation. Issue 8 (1st August 1998) - Wolf, Sebastian; Werner, Eva; Schulte, Karin; Reim, Martin
Abstract : AIM: To assess the effect of topical and systemic application of a β adrenergic receptor blocker on retinal haemodynamics. METHODS: 24 healthy subjects were included in this double masked, randomised, placebo controlled crossover study. Metipranolol, a non-selective β adrenergic receptor blocking agent was used as test drug. In all subjects arm-retina time, arteriovenous passage time, arterial mean dye velocity, the arterial vessel diameters, and capillary flow velocity were quantified from digital video fluorescein angiograms. RESULTS: A significant effect was observed on the arteriovenous passage time (p<0.05), the arterial mean dye bolus velocity (p<0.05), and capillary blood velocity (p<0.05), but not on the arterial vessel diameter. The arterial mean dye bolus velocity and capillary blood velocity increased after application of the test drug (topical and systemic). In tandem with this a decrease of the arteriovenous passage time was observed. The perfusion pressure increased after topical application and remained unchanged after systemic application of metipranolol. CONCLUSIONS: This study shows that systemic as well as topical application of metipranolol leads to increased retinal blood flow velocities. The implications of these results for treatment with β adrenergic receptor blockers is not clear. However, in view of these data it is very unlikely that treatment with metipranolol has a negative effect on retinal blood flow.